2021
DOI: 10.1001/jamaneurol.2020.3536
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Alzheimer Disease Risk Loci and Pathways in African American Individuals Using the African Genome Resources Panel

Abstract: IMPORTANCECompared with non-Hispanic White individuals, African American individuals from the same community are approximately twice as likely to develop Alzheimer disease. Despite this disparity, the largest Alzheimer disease genome-wide association studies to date have been conducted in non-Hispanic White individuals. In the largest association analyses of Alzheimer disease in African American individuals, ABCA7, TREM2, and an intergenic locus at 5q35 were previously implicated. OBJECTIVETo identify addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
148
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(175 citation statements)
references
References 85 publications
9
148
0
Order By: Relevance
“…More recently, genetic knockdown of heparan sulfate-modifying enzyme hse-5 in C. elegans mitigated TDP-43 induced deficits in synaptic transmission [ 55 ], further suggesting a link between TDP-43 pathology, neurodegeneration and heparan sulfate proteoglycans such as Dlp/GPC6. Lastly, in the last year, genome wide association studies have identified GPC6 as a risk factor multiple sclerosis [ 80 ] and for Alzheimer’s in African Americans [ 51 ] further suggesting a role for GPC6 in maintaining neuronal function.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, genetic knockdown of heparan sulfate-modifying enzyme hse-5 in C. elegans mitigated TDP-43 induced deficits in synaptic transmission [ 55 ], further suggesting a link between TDP-43 pathology, neurodegeneration and heparan sulfate proteoglycans such as Dlp/GPC6. Lastly, in the last year, genome wide association studies have identified GPC6 as a risk factor multiple sclerosis [ 80 ] and for Alzheimer’s in African Americans [ 51 ] further suggesting a role for GPC6 in maintaining neuronal function.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance to this review, SNP variant rs62039712 (NC_000016.9: g.79355857G>A) mapping to the WWOX locus reached genome-wide significance ( p = 3.7 × 10 −8 ) with an OR of 1.16 [ 10 ]. The identification of WWOX as a novel AD risk gene is further supported by a recently published meta-analysis with the goal of identifying novel AD risk loci in African American individuals [ 60 ]. The authors identified several novel loci of genome-wide significance for individuals of African American ancestry.…”
Section: Wwox-associated Cns Disordersmentioning
confidence: 99%
“…The authors identified several novel loci of genome-wide significance for individuals of African American ancestry. Interestingly, of the 25 previously identified AD loci in non-Hispanic White individuals [ 10 ], WWOX was found among only 7 loci that were implicated at a nominal significance level in African American individuals, suggesting that this gene may participate in cellular pathways associated with AD common to both ancestries [ 60 ].…”
Section: Wwox-associated Cns Disordersmentioning
confidence: 99%
“…AAs are more likely to experience kidney failure and disease compared to CAs (Harding et al, 2017). Indeed, a recent genome‐wide association meta‐analysis suggested a genetic link between kidney system function and risk of Alzheimer's disease in AAs (Kunkle et al, 2021). Given the strong relationship between kidney function and BP (Young et al, 2002), genetic differences linked with kidney function between the race groups might have been associated with the interaction between race and MAP in the present study.…”
Section: Discussionmentioning
confidence: 99%